ANALYSIS OF THE AFFECT OF FINANCIAL PERFORMANCE INDICATORS ON STOCK RETURN BANKING IN INDONESIA STOCK EXCHANGE PERIOD 2011-2017 - Yemniati
Investor interest in a bank's stock is based on its belief in Banking performance. The general way that is used to see the performance appropriateness of a Banking is by analyzing its financial performance and the return that will be received on the investment in the stock. This study aims to analyze the affect of Capital Adequacy Ratio (CAR), Net Performing Loans (NPL), Return on Assets (ROA), Net Interest Margin (NIM), Operating Cost for Operating Income (BOPO), Loan to Deposit Ratio (LDR), Return on Equity (ROE) on Stock Return. Sampling is done by purposive sampling method, with the criteria of banking companies listed on the Indonesia Stock Exchange. The samples taken were 18 commercial banks. This analysis uses panel data regression and linear regression methods to analyze the dependent variable and the independent variable. The calculation results show that the significant affect on stock return is the variable Capital Adequacy Ratio (CAR), Net Performing Loans (NPL), Return on Assets (ROA), and Return on Equity (ROE) while those that have no significant affect are variables Net Interest Margin (NIM) and Operating Cost for Operating Income (BOPO).